2022
DOI: 10.1101/2022.06.08.495292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell multi-omics defines the cell-type specific impact of splicing aberrations in human hematopoietic clonal outgrowths

Abstract: RNA splicing factors are recurrently affected by alteration-of-function mutations in clonal blood disorders, highlighting the importance of splicing regulation in hematopoiesis. However, our understanding of the impact of dysregulated RNA splicing has been hampered by the inability to distinguish mutant and wildtype cells in primary patient samples, the cell-type complexity of the hematopoietic system, and the sparse and biased coverage of splice junctions by short-read sequencing typically used in single-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…115 The simultaneous single-cell profiling of gene expression, cell surface protein markers, and somatic mutation status is now possible and has been used to investigate the impact of splicing aberrations in human age-related clonal hematopoiesis by combing Genotyping of Transcriptomes (GoT), utilizing long-read single-cell transcriptome profiling in addition to proteo-genomics using CITE-Seq. 116 Assessment of bone marrow progenitor cells derived from patients with defective RNA splicing, due to mutations of the core RNA splicing factor 3b subunit 1 (SF3B1), was shown to have a fitness advantage over WT SF3B1 cells, resulting in the expansion of a mutant population of erythroid progenitor cells, which displayed an upregulation of genes involved in the cell cycle and mRNA translation. 116 Moreover, another study using a multiomics approach to interrogate human clonal hematopoiesis combined scBS-Seq with scRNA-Seq and targeted DNMT3A genotyping.…”
Section: Multiomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…115 The simultaneous single-cell profiling of gene expression, cell surface protein markers, and somatic mutation status is now possible and has been used to investigate the impact of splicing aberrations in human age-related clonal hematopoiesis by combing Genotyping of Transcriptomes (GoT), utilizing long-read single-cell transcriptome profiling in addition to proteo-genomics using CITE-Seq. 116 Assessment of bone marrow progenitor cells derived from patients with defective RNA splicing, due to mutations of the core RNA splicing factor 3b subunit 1 (SF3B1), was shown to have a fitness advantage over WT SF3B1 cells, resulting in the expansion of a mutant population of erythroid progenitor cells, which displayed an upregulation of genes involved in the cell cycle and mRNA translation. 116 Moreover, another study using a multiomics approach to interrogate human clonal hematopoiesis combined scBS-Seq with scRNA-Seq and targeted DNMT3A genotyping.…”
Section: Multiomicsmentioning
confidence: 99%
“…116 Assessment of bone marrow progenitor cells derived from patients with defective RNA splicing, due to mutations of the core RNA splicing factor 3b subunit 1 (SF3B1), was shown to have a fitness advantage over WT SF3B1 cells, resulting in the expansion of a mutant population of erythroid progenitor cells, which displayed an upregulation of genes involved in the cell cycle and mRNA translation. 116 Moreover, another study using a multiomics approach to interrogate human clonal hematopoiesis combined scBS-Seq with scRNA-Seq and targeted DNMT3A genotyping. This study showed that mutations within DNMT3A resulted in a myeloid over lymphoid bias and that these DNMT3A mutations revealed patterns of selective hypomethylation of key hematopoietic transcription factors that results in the disruption of early progenitor states.…”
Section: Multiomicsmentioning
confidence: 99%
“…Pellagatti et al (2018) [174] explored the impact of mutations in splicing factors applying bulk RNA-seq to the study of differentially expressed isoforms. Finally, an interesting work by Gaiti et al [175], still unpublished, combines scRNA-seq with single cell genomics to shed light on the effects of an specific spliceosome mutation: SF3B1, on gene and isoform expression. With these methods, they are able to detect aberrant splicing in mutated cells occurring in a cell type-specific manner.…”
Section: Transcriptomics In Hematopoiesismentioning
confidence: 99%